Вклад академіка А.М. Гродзінського у розвиток теорії та практики інтродукції рослин і созології - Cherevchenko, T.M.; Moroz, P.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Contribution of Academician A.M. Grodzinsky to development of theory and methods of plant introduction, rare and vanishing plant species conservation, use of plants as alternative energy source, environment protection are elucidated. Original ideas and foresights of the scientist are confirmed by the results of practical activity of his followers.